Testing the limits of plant drought stress and subsequent recovery in four provenances of a widely distributed subtropical tree species. (14th January 2022) - Duan, Honglang; Resco de Dios, Víctor; Wang, Defu; Zhao, Nan; Huang, Guomin; Liu, Wenfei; Wu, Jianping; Zhou, Shuangxi; Choat, Brendan; Tissue, David T.
Abstract: Drought‐induced tree mortality may increase with ongoing climate change. Unraveling the links between stem hydraulics and mortality thresholds, and the effects of intraspecific variation, remain important unresolved issues. We conducted a water manipulation experiment in a rain‐out shelter, using four provenances of Schima superba originating from a gradient of annual precipitation (1124–1796 mm) and temperature (16.4–22.4°C). Seedlings were droughted to three levels of percentage loss of hydraulic conductivity (i.e., P 50, P 88  and P 99) and subsequently rewatered to field capacity for 30 days; traits related to water and carbon relations were measured. The lethal water potential associated with incipient mortality was between P 50 and P 88 . Seedlings exhibited similar drought responses in xylem water potential, hydraulic conductivity and gas exchange. Upon rehydration, patterns of gas exchange differed among provenances but were not related to the climate at the origin. The four provenances exhibited a similar degree of stem hydraulic recovery, which was correlated with the magnitude of antecedent drought and stem soluble sugar at the end of the drought. Results suggest that there were intraspecific differences in the capacity of S. superba seedlings for carbon assimilation during recovery, indicating a decoupling between gas exchange recovery and stem hydraulics across provenances. Summary Statement: Schima superba may start to die between P 50 and P 88, with mortality being more likely than survival after P 88 . There were intraspecific differences in the capacity for carbon assimilation during recovery, indicating a decoupling between gas exchange recovery and stem hydraulics across provenances.